The Role of Alternatives in Language - Repp, Sophie; Spalek, Katharina (Frontiers in Communication, 2021)
In this review we provide a discussion of the concept of alternatives and its role in linguistic and psycholinguistic theorizing in the context of the contributions that have appeared in the Frontiers Research Topic 'The Role of Alternatives in Language'. We are discussing the linguistic phenomena for which alternatives have been argued to play a paramount role: negation, counterfactual sentences, scalar implicatures and exhaustivity, focus, contrastive topics, and sentences with bare plurals and with definite plurals. We review in how far alternatives are relevant for these phenomena and how this relevance has been captured by theoretical linguistic accounts. Regarding the psycholinguistic side of alternatives, we discuss the mental activation of alternatives: its time course, its mandatory vs. optional nature. We also address the methodological issue of how experimental studies can operationalize alternatives. Finally, we explore the phenomenon of individual variation, which increasingly attracts attention in linguistics. In sum, this review gives an inclusive and broad discussion of alternatives by bringing together different research strands whose findings and theoretical proposals can advance our knowledge of alternatives in inspiring cross-fertilization.